2013
DOI: 10.1016/j.addbeh.2013.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming recruitment challenges of web-based interventions for tobacco use: The case of web-based acceptance and commitment therapy for smoking cessation

Abstract: Web-based behavioral interventions for substance use are being developed at a rapid pace, yet there is a dearth of information regarding the most effective methods for recruiting participants into web-based intervention trials. In this paper, we describe our successful recruitment of participants into a pilot trial of web-based Acceptance and Commitment Therapy (ACT) for smoking cessation and compare traditional and web-based methods of recruitment in terms of their effects on baseline participant characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(84 citation statements)
references
References 11 publications
3
76
0
Order By: Relevance
“…Our findings show that to a certain extent it was feasible to use a primary care approach to recruit and consent people who smoke to the study, although recruitment took a long time, and we only recruited 87 % of our target sample size (87/100). There has only been limited previous research into the optimum recruitment of participants to internet-based smoking cessation interventions, with a recent study suggesting the benefit of a combination of offline and online routes [23], and other studies have shown that online only approaches can yield high recruitment [24]. Our questionnaire responses suggest that the eligibility criteria were not always applied correctly: some smokers had already given up, while others had little desire to quit.…”
Section: Discussionmentioning
confidence: 87%
“…Our findings show that to a certain extent it was feasible to use a primary care approach to recruit and consent people who smoke to the study, although recruitment took a long time, and we only recruited 87 % of our target sample size (87/100). There has only been limited previous research into the optimum recruitment of participants to internet-based smoking cessation interventions, with a recent study suggesting the benefit of a combination of offline and online routes [23], and other studies have shown that online only approaches can yield high recruitment [24]. Our questionnaire responses suggest that the eligibility criteria were not always applied correctly: some smokers had already given up, while others had little desire to quit.…”
Section: Discussionmentioning
confidence: 87%
“…Out of 30 studies, 12 studies (40%) reported higher rates of recruitment through social media as compared with any of the other methods used [14-17,26,28,31,32,35, 36,41,42] and 15 studies (50%) reported recruitment via social media to be less effective than at least one other method used [18-21,23-25, 27,33-35,37-40]. Heffner et al [20] and Rabin et al [24] found social media to be the least effective method out of multiple (>2) recruitment methods used. Rabin et al [24] were unable to recruit a single participant via social media.…”
Section: Resultsmentioning
confidence: 99%
“…Based on prior success in national recruitment for a web-delivered trial (Heffner et al, 2013), we used both web-based and traditional methods of recruitment. Recruitment sources were: 39% from Facebook ads, 38% from press-release generated media (13% TV, 10% radio, 8% websites, 7% newspaper), and 23% from other sources (7% Google ads, 5% search engine results, 4% fhcrc.org, 7% other).…”
Section: Methodsmentioning
confidence: 99%